2016
DOI: 10.1785/0220150211
|View full text |Cite
|
Sign up to set email alerts
|

Rate‐Dependent Incompleteness of Earthquake Catalogs

Abstract: Important information about the earthquake generation process can be gained from instrumental earthquake catalogs, but this requires complete recordings to avoid biased results. The local completeness magnitude M c is known to depend on general conditions such as the seismographic network and the environmental noise, which generally limit the possibility of detecting small events. The detectability can be additionally reduced by an earthquake-induced increase of the noise level leading to shortterm variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 46 publications
7
114
0
Order By: Relevance
“…The value of max( M c ( t )) strongly depends on the estimation method. Hainzl [] found for sample sizes of 10 a maximum of approximately M c = 4.5 for the Landers and Hector Mine sequences. Other studies found max ( M c ( t )) ≈ 4–4.5 with different methods [ Kagan , ; Helmstetter et al ., ].…”
Section: Datamentioning
confidence: 99%
“…The value of max( M c ( t )) strongly depends on the estimation method. Hainzl [] found for sample sizes of 10 a maximum of approximately M c = 4.5 for the Landers and Hector Mine sequences. Other studies found max ( M c ( t )) ≈ 4–4.5 with different methods [ Kagan , ; Helmstetter et al ., ].…”
Section: Datamentioning
confidence: 99%
“…One observational approach is to use waveformbased earthquake detection methods (e.g., Enescu et al 2007Enescu et al , 2009Peng et al 2007;Marsan and Enescu 2012;Hainzl 2016). These methods found many aftershocks that are unrecorded in the catalog.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting µ-value shows some strong fluctuations which might suggest an episodic character of the aseismic forcing. Nevertheless some fluctuations could also be partially related to missing events in phases of activity (Hainzl 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed aftershock studies showed that the delay parameter c is very small, in the order of one to several minutes or even less (.e.g. Peng et al 2006;Enescu et al 2007), while larger estimations often result from incomplete recordings directly after the occurrence of larger earthquakes (Kagan 2004, Hainzl 2016. Note that for single aftershock decay according to the Omori-Utsu law, the probability density function of the interevent-times decays with an exponent of 2 − 1 p (see above).…”
Section: Etas Analysismentioning
confidence: 99%